Cyanobacteria of High Wetlands from Northwestern Argentina - Mirande, Virginia (2015)
The latitudinal and altitudinal variability of our country allows the existence of a diversity of wetlands that in a broadest sense, including marsh, fen, peatland or flowing or static water-covered surfaces, permanent or temporary, natural or artificial, brackish or salt, as well as areas of marine water where the depth not exceed six meters at low tide. The objective of this paper was to contribute to knowledge of Cyanobacteria in High Wetlands from Northwest of Argentina. An interdisciplinary sampling was realized in Summary, from 21 on January to 01 on February, and twentisix lakes were studied corresponding to Jujuy, Salta and Catamarca provences. The qualitative samples were collected with plankton net of 20 µm and filtering of 25 litres of water. These samples were fixed in situ with formaldehyde 4% and observed with binocular microscopy and drawing camera in laboratory. According of results obtained the taxocenoses was formed by 23 taxa specially cosmopolites and brackish environments belong to Chroococcales (5), Nostocales (3) and Oscillatoriales (15). We described for the first time Phormidium inundatum in the Northwest of Argentina and, apart of this specie, Merismopedia glauca, M. punctata, Synechococcus elongatus, Anabaena variabilis, Nodularia spumigena, Nostoc linckia, Leptolyngbya fragilis, Spirulina major, Phormidium autumnale, P. breve and P. Molle for the Catamarca Province.